THEORETICAL BASES OF FORMATION OF SCIENCE RESEARCH COMPETENCE OF FUTURE BIOLOGISTS (iN PRACTICE «RESOURCES OF MEDICINAL PLANTS») - A. KYRBASSOVA , Elzira; DYUSKALIEVA , G.U.; КENESBAYEV, S.M. (SSD Journal, 2018)
The article presents the theoretical basis for the formation of science research competence of future biologists in the pedagogical university. Today the students research work is one of the most important components in the preparation of specialists in high school, it becomes an organic component of the entire educational process. In this regard, it is necessary to build it so that students not only receive a certain amount of knowledge in accordance with the program, but also develop a desire for self-search, improvement of knowledge, set them to master research methods, non-standard methods of solving scientific problems, to teach to analyze and summarize the flow of various information.The main task of the teacher in the organization of research activities-to develop motivation to attract students to join the activities. Teacher is the main organizer and coordinator of creative activity of students. High professionalism of teachers, pedagogical skills give rise to the student's interest and desire to participate in scientific researchwork, as a result of which the cognitive activity sharply increases, which also acquires a creative character [1]. Research work of students, undergraduates is a complex of activities aimed at the development of methods and skills for research papers. Development and improvement of the research works of students is the main task of pedagogics associated with the activation of cognitive activity of students, the ability of creative thinking and the formation of research competence skills. Within the framework of the innovative educational process, the research activity of University students becomes more and more relevant and becomes one of the main components of the training of future specialists [2]. Research competence of students-the readiness of the individual formed in the process of research activities. This include scientific values and norms, the development of universal methods of research, independent mastering of new knowledge, knowledge of new methods of obtaining results, the implementation of the reflection of research activities, the readiness of pedagogical and psychological research [3]. Scientific work of students in higher educational institutions forms professional and creative skills of modern specialists capable of effectively solving theoretical and applied problems [4]. The formation of research activities of students and undergraduates of biological specialty occurs in all periods of training the study of binding and elective disciplines. Each discipline has its own characteristics. For example, interdisciplinary connections of the discipline "Resources of medicinal plants", studied by graduate students of biology are very extensive. It is closely linked to botany, ecology, genetics, chemistry, history, medicine, etc. In this regard, the laboratory work of the discipline "Resources of medicinal plants" held in different directions.